2003
DOI: 10.1038/nature01894
|View full text |Cite
|
Sign up to set email alerts
|

Generation of prion transmission barriers by mutational control of amyloid conformations

Abstract: Self-propagating beta-sheet-rich protein aggregates are implicated in a wide range of protein-misfolding phenomena, including amyloid diseases and prion-based inheritance. Two properties have emerged as common features of amyloids. Amyloid formation is ubiquitous: many unrelated proteins form such aggregates and even a single polypeptide can misfold into multiple forms--a process that is thought to underlie prion strain variation. Despite this promiscuity, amyloid propagation can be highly sequence specific: a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
97
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 27 publications
8
97
0
Order By: Relevance
“…Such behavior would be consistent with the recently described ability of certain yeast prion proteins to make amyloid fibrils that exhibit different seeding capabilities depending on the details of how the seeding fibrils are generated (18,61) and, more broadly, could provide the underlying structural basis for species barriers and strain phenomena in prion infectivity (18 -20,61).…”
Section: Discussionsupporting
confidence: 57%
“…Such behavior would be consistent with the recently described ability of certain yeast prion proteins to make amyloid fibrils that exhibit different seeding capabilities depending on the details of how the seeding fibrils are generated (18,61) and, more broadly, could provide the underlying structural basis for species barriers and strain phenomena in prion infectivity (18 -20,61).…”
Section: Discussionsupporting
confidence: 57%
“…It has been suggested that the morphology of fibrils can be propagated by seeding (23)(24)(25)(26). This was true for the sonication-induced fibrils, since the F3 and F4 fibrils had the same morphology and secondary structure as the F2 fibrils, i.e.…”
Section: Ultrasonication-induced Fibrilmentioning
confidence: 83%
“…Although we do not know the precise structure of the amyloid fibrils prepared from the heterologous seeds, critical differences were observed in the fibril diameters between seeded and non-seeded fibrils in the present study. From a view point of structural changes influenced by fibril additives, it is interesting to note the report that changes in the specific structure of fibrils, caused either by mutation (68) or other extrinsic factors (69), are implicated in the onset of prion-like behavior of Sup35. Such changes in the fibril structure might be caused by fibril seeds of the same protein (in the case of Sup35) or different proteins (in the case of the present experiments).…”
Section: Discussionmentioning
confidence: 99%